Pengaruh Good Corporate Governance dan Pandemi Covid-19 terhadap Financial Distress - Herry Hernandes; Rizky Eriandani (Universitas Pamulang, 2023)
This research aims to provide information and prove empirically on the effect of good corporate governance (board size, institutional ownership, and managerial ownership) and the Covid-19 pandemic period on financial difficulties. This research is different from previous research because it adds the variable of the Covid-19 pandemic. This is due to the Covid-19 pandemic which has affected the country's economy so that researchers will look at the influence of Covid-19 in Indonesia. This study uses data for the period 2018 to 2021, the source of which is from the financial and annual reports of companies that have been listed on the Indonesia Stock Exchange. This study has 4 hypotheses that were tested with logistic regression. Because the dependent variable is categorical. The results of this study state that board size, institutional ownership, and the Covid-19 pandemic have an influence on financial distress. besides that, managerial ownership has no effect on financial distress